2006
DOI: 10.1186/1471-2148-6-17
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny and taxonomic revision of the sportive lemurs (Lepilemur, Primates)

Abstract: Background: The number of species within the Malagasy genus Lepilemur and their phylogenetic relationships is disputed and controversial. In order to establish their evolutionary relationships, a comparative cytogenetic and molecular study was performed. We sequenced the complete mitochondrial cytochrome b gene (1140 bp) from 68 individuals representing all eight sportive lemur species and most major populations, and compared the results with those obtained from cytogenetic studies derived from 99 specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Pastorini et al (2003) suggested that the forms either side of the Tsiribihina River were different species. Andriaholinirina et al (2006a) confirmed their suspicion, describing Lepilemur randrianasoli as occurring north of Tsiribihina River, possibly to the Manambaho or Mahavavy du Sud rivers. The range of Lepilemur ruficaudatus is possibly now limited to the south of the Tsiribihina River, south to the Onilahy River, where it is replaced by Lepilemur leucopus (cf.…”
Section: Family Cheirogaleidae Gray 1873mentioning
confidence: 51%
See 4 more Smart Citations
“…Pastorini et al (2003) suggested that the forms either side of the Tsiribihina River were different species. Andriaholinirina et al (2006a) confirmed their suspicion, describing Lepilemur randrianasoli as occurring north of Tsiribihina River, possibly to the Manambaho or Mahavavy du Sud rivers. The range of Lepilemur ruficaudatus is possibly now limited to the south of the Tsiribihina River, south to the Onilahy River, where it is replaced by Lepilemur leucopus (cf.…”
Section: Family Cheirogaleidae Gray 1873mentioning
confidence: 51%
“…To the south it occurs as far as the Ankarafa Forest on the Sahamalaza Peninsula (Randriatahina and Rabarivola 2004). However, in their description of Lepilemur sahamalazensis, Andriaholinirina et al (2006a) restrict L. dorsalis to Nosy Be, Ambanja and regions north of the Sambirano River, probably to the Mahavavy du Nord River, and the range of L. ankaranensis. Lepilemur sahamalazensis and L. dorsalis are the only sportive lemurs to have a diploid chromosome number of 26 (Andriaholinirina et al 2006a).…”
Section: Family Cheirogaleidae Gray 1873mentioning
confidence: 99%
See 3 more Smart Citations